Cow's milk protein allergy in children: a practical guide - Calzone Luigi; Baldi Francesco; Bendandi Barbara; Caffarelli Carlo; Marani Miris; Pasquinelli Pamela (BMC, 2010)
Abstract A joint study group on cow's milk allergy was convened by the Emilia-Romagna Working Group for Paediatric Allergy and by the Emilia-Romagna Working Group for Paediatric Gastroenterology to focus best practice for diagnosis, management and follow-up of cow's milk allergy in children and to offer a common approach for allergologists, gastroenterologists, general paediatricians and primary care physicians. The report prepared by the study group was discussed by members of Working Groups who met three times in Italy. This guide is the result of a consensus reached in the following areas. Cow's milk allergy should be suspected in children who have immediate symptoms such as acute urticaria/angioedema, wheezing, rhinitis, dry cough, vomiting, laryngeal edema, acute asthma with severe respiratory distress, anaphylaxis. Late reactions due to cow's milk allergy are atopic dermatitis, chronic diarrhoea, blood in the stools, iron deficiency anaemia, gastroesophageal reflux disease, constipation, chronic vomiting, colic, poor growth (food refusal), enterocolitis syndrome, protein-losing enteropathy with hypoalbuminemia, eosinophilic oesophagogastroenteropathy. An overview of acceptable means for diagnosis is included. According to symptoms and infant diet, three different algorithms for diagnosis and follow-up have been suggested.